Comparative nasal effects of bradykinin and histamine: influence on nasal airways resistance and plasma protein exudation. Issue 4 (April 1993) - Rajakulasingam, K; Polosa, R; Lau, L C; Church, M K; Holgate, S T; Howarth, P H
Abstract : BACKGROUND–Bradykinin may contribute to the pathogenesis of allergic rhinitis. Like histamine, nasal challenge with bradykinin induces rhinorrhoea, nasal blockage, and plasma protein leakage. Their comparative nasal potencies have not, however, been fully elucidated. METHODS–Three double blind, randomised, placebo controlled and cross-over studies were undertaken to compare objectively the nasal effects of bradykinin, histamine, and vehicle. RESULTS–Both bradykinin and histamine produced dose dependent increases in nasal airways resistance (NAR). There was no significant difference in the effects of bradykinin and histamine on NAR at any dose level. On a molar basis, however, bradykinin was 6.98 times more potent than histamine in inducing a 50% increase in NAR. Nasal challenge with bradykinin and histamine also induced significant rhinorrhoea compared with vehicle. The amount of rhinorrhoea induced by histamine was significantly greater than that induced by bradykinin at any dose level. Bradykinin and histamine induced dose dependent nasal pain and nasal itch respectively. When administered as single doses both bradykinin (1.9 mumol) and histamine (1.9 mumol) induced significant rhinorrhoea compared with the vehicle. The volume of rhinorrhoea secretions induced by histamine was 29% greater than that induced by bradykinin. In contrast, although NAR was increased significantly more by histamine than by the vehicle, the effect of bradykinin on NAR was significantly greater than histamine and vehicle in both magnitude and duration of effect. The incremental effect of bradykinin on lavage albumin levels was also significantly greater than both histamine and vehicle. CONCLUSIONS–This study shows that the nasal vascular effects of histamine are less prominent than its actions on rhinorrhoea, and that the greater obstructive effect of bradykinin than histamine on NAR may contribute to the relative lack of efficacy of H1 antihistamines on nasal blockage in clinical disease.